Neurose - Causes and Mechanisms of Development, Symptoms, Treatment, Prevention - Azizbek, Murodov; Rizakul, Uktamov; Parvina, Murodullayeva; Ziyodulloyevna, Xakimova Soxiba (Journal of Science in Medicine and Life, 2024)
Neurosis, psychoneurosis, neurotic disorder, neurosis disease (new Latin neurosis from ancient Greek. neuron "nerve") is a complex of long-lasting functional psychogenic disorders. The clinical picture of such disorders is characterized by asthenic, restless thoughts or signs of hysteria, as well as a temporary decrease in mental and physical work capacity. The term "neurosis" is not currently used by the professional psychiatric community in the United States. Starting with the third edition of the DSM-III in 1980, the "neuroses" section of the American Diagnostic and Statistical Manual of Mental Disorders was abolished. For example, dysthymic disorder instead of depressive neurosis, obsessive-compulsive disorder instead of obsessive-compulsive neurosis, hypochondria instead of hypochondriac neurosis. Psychoanalytic theories represent neurosis and its symptoms mainly as the result of a deep psychological conflict. It is assumed that such a conflict is formed in the conditions of long-standing social situations that prevent the satisfaction of basic needs of a person and threaten his future.